2017
DOI: 10.1080/10401334.2017.1330690
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perceptions of Trigger Warnings in Medical Education

Abstract: Of the 424 medical students invited to participate, 259 completed the survey (M = 24.8 years, SD + 3.4, 51.4% female, 76.1% White, 53.7% 1st-year students). Few students (11.2%) were aware of the term trigger warning and its definition. However, after being presented with a formal definition on the online survey, 38.6% reported having had a professor use one. When asked whether they supported the use of trigger warnings in medical education, respondents were distributed fairly equally by response (yes = 31.0%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 39 publications
1
45
0
Order By: Relevance
“…In addition, it appears that both instructor and student attitudes towards trigger warnings are mixed [11][12][13][14]. For example, when asked whether they supported the use of trigger warnings in their training, medical students were evenly split among the options [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it appears that both instructor and student attitudes towards trigger warnings are mixed [11][12][13][14]. For example, when asked whether they supported the use of trigger warnings in their training, medical students were evenly split among the options [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it appears that both instructor and student attitudes towards trigger warnings are mixed [11][12][13][14]. For example, when asked whether they supported the use of trigger warnings in their training, medical students were evenly split among the options [13]. Psychology students across both public and private institutions showed similar ambivalence, as some appreciated their potential value but were concerned that avoidance of triggering topics by instructors might limit their learning [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…While there is some evidence to support the value of classroom topics that can potentially trigger intrusive distress and the use of trigger warnings in alerting and preparing students (Beverly et al . ), robust evidence is needed on how to effectively facilitate such discussions (Boysen ).…”
Section: Discussionmentioning
confidence: 99%
“…48 A 2018 study of content warnings in medical school revealed few students (11%) were aware of what a content or trigger warning is, and fewer than one-third supported their use in medical education. 49 However, the number of undergraduate Plochocki 3 students reporting concerns to administrators about failure of faculty to implement content warnings is on the rise and may appear in medical education in greater numbers. 50 Some medical professionals have already begun to advocate for the creation of safe spaces where discomforting subjects can be discussed.…”
Section: Learning Environmentsmentioning
confidence: 99%